Spatial distribution of aquatic marine fungi across the western Arctic and sub‐arctic. (7th July 2016) - Hassett, Brandon T.; Ducluzeau, Anne‐Lise L; Collins, Roy E.; Gradinger, Rolf
Summary: Fungi are important parasites of primary producers and nutrient cyclers in aquatic ecosystems. In the Pacific‐Arctic domain, fungal parasitism is linked to light intensities and algal stress that can elevate disease incidence on algae and reduce diatom concentrations. Fungi are vastly understudied in the marine realm and knowledge of their function is constrained by the current understanding of fungal distribution and drivers on global scales. To investigate the spatial distribution of fungi in the western Arctic and sub‐Arctic, we used high throughput methods to sequence 18S rRNA, cloned and sequenced 28S rRNA and microscopically counted chytrid‐infected diatoms. We identified a broad distribution of fungal taxa predominated by Chytridiomycota and Dikarya. Phylogenetic analysis of our Chytridiomycota clones placed Arctic marine fungi sister to the order Lobulomycetales. This clade of fungi predominated in fungal communities under ice with low snowpack. Microscopic examination of fixed seawater and sea ice samples revealed chytrids parasitizing diatoms collected across the Arctic that notably infected 25% of a single diatom species in the Bering Sea. The Pezizomycotina comprised > 95% of eukaryotic sequence reads in Greenland, providing preliminary evidence for osmotrophs being a substitute for algae as the base of food webs.